Microenvironmental interference with intra-articular stem cell regeneration influences the onset and progression of arthritis - Shao, Zhuce; Wang, Benlong; Gao, Huanshen; Zhang, Shenqi (Frontiers in Genetics, 2024)
Studies have indicated that the preservation of joint health and the facilitation of damage recovery are predominantly contingent upon the joint's microenvironment, including cell-cell interactions, the extracellular matrix's composition, and the existence of local growth factors. Mesenchymal stem cells (MSCs), which possess the capacity to self-renew and specialize in many directions, respond to cues from the microenvironment, and aid in the regeneration of bone and cartilage, are crucial to this process. Changes in the microenvironment (such as an increase in inflammatory mediators or the breakdown of the extracellular matrix) in the pathological context of arthritis might interfere with stem cell activation and reduce their ability to regenerate. This paper investigates the potential role of joint microenvironmental variables in promoting or inhibiting the development of arthritis by influencing stem cells' ability to regenerate. The present status of research on stem cell activity in the joint microenvironment is also outlined, and potential directions for developing new treatments for arthritis that make use of these intervention techniques to boost stem cell regenerative potential through altering the intra-articular environment are also investigated. This review's objectives are to investigate these processes, offer fresh perspectives, and offer a solid scientific foundation for the creation of arthritic treatment plans in the future.